2015
DOI: 10.1111/all.12580
|View full text |Cite|
|
Sign up to set email alerts
|

Sputum periostin in patients with different severe asthma phenotypes

Abstract: This study demonstrates the utility of periostin in phenotyping severe asthma. Periostin levels in sputum are associated with persistent airflow limitation in asthma patients with airway eosinophilia despite treatment with high-dose inhaled corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
57
2
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 25 publications
12
57
2
4
Order By: Relevance
“…This is in contrast to studies assessing periostin in induced sputum, which demonstrated the association of periostin levels with asthma severity or the presence of fixed bronchial obstruction as well as with the percentage of eosinophils in the blood and sputum2023 However, our asthmatic patients with CRS who reported symptoms during the previous 3 months had on average 50% higher levels of periostin in EBC than those without. Patients with and without CRS symptoms were similar with respect to all clinical/pathophysiological features of asthma, including severity, asthma control, or spirometry.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to studies assessing periostin in induced sputum, which demonstrated the association of periostin levels with asthma severity or the presence of fixed bronchial obstruction as well as with the percentage of eosinophils in the blood and sputum2023 However, our asthmatic patients with CRS who reported symptoms during the previous 3 months had on average 50% higher levels of periostin in EBC than those without. Patients with and without CRS symptoms were similar with respect to all clinical/pathophysiological features of asthma, including severity, asthma control, or spirometry.…”
Section: Discussioncontrasting
confidence: 99%
“…Concentrations of periostin were similar in EBC, as well as in serum, collected from patients with asthma and healthy individuals, which is difficult to explain because in previous studies increased levels of this molecule have been found in induced sputum and were associated with eosinophilic airway inflammation 20. It seems likely that EBC and serum levels of periostin in our asthma patients were affected by chronic asthma treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Bobolea et al46 showed a good correlation of sputum periostin with late-onset asthma. It is generally known that late-onset asthma is eosinophil-dominant and is more often non-atopic than childhood asthma 47.…”
Section: Introductionmentioning
confidence: 95%
“…According to some authors, this protein is a safe and stable biomarker of chronic inflammation [17] and of the T H 2 mechanism underlying severe asthma in adults [10]. A link has been established between periostin and bronchial obstruction, elevated levels of fractional exhaled nitric oxide (FeNO), and eosinophil count in adults [18][19][20]. One of the effects of periostin is to attract inflammatory cells-neutrophils or eosinophils-to the airway.…”
Section: Introductionmentioning
confidence: 99%